Optimizing Information System Utilization through Strategic Planning using Ward-Peppard and Cassidy Methodology - Kharis Syaban; Hamsinar, Henny (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
This research aims to optimize the utilization of information systems (IS) at Universitas Sembilanbelas November Kolaka through a strategic planning approach using the Ward-Peppard and Cassidy Methods. In the context of globalization and intense competition in higher education, appropriate strategies in IS management are crucial for institutional success. The Ward-Peppard and Cassidy Methods are used to design an IS strategic plan integrated with the organization's goals. The methodological steps include analysing the university's internal and external environment, identifying stakeholder needs and expectations, and formulating IS strategies that consider available resources and future development directions. A case study was conducted at Universitas Sembilanbelas November Kolaka, using a qualitative approach involving in-depth interviews with university leaders, administrative staff, and IS users. The research findings identify challenges in IS utilization, including a lack of integration between existing systems, the need for human resource skills development, and the maintenance of high-quality IT infrastructure. This study provides a comprehensive view of the IS strategies needed to enhance operational effectiveness and achieve the university's strategic goals. The practical implications of this research are the development of an action plan that can help the university manage and optimize their IS investments more effectively